1999
DOI: 10.2527/1999.7782172x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary levels of selenium-enriched yeast and sodium selenite as selenium sources fed to growing-finishing pigs on performance, tissue selenium, serum glutathione peroxidase activity, carcass characteristics, and loin quality.

Abstract: This research evaluated the efficacy of inorganic and organic Se sources for growing-finishing pigs, as measured by performance and various tissue, serum, carcass, and loin quality traits. A total of 351 crossbred pigs were allotted at an average BW of 20.4 kg to six replicates of a 2x4 factorial experiment in a randomized complete block design. Pigs were fed diets containing Se-enriched yeast (organic) or sodium selenite (inorganic), each at .05, .10, .20, or .30 mg Se/kg diet. A non-Se-fortified basal diet w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
171
3
14

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(233 citation statements)
references
References 0 publications
45
171
3
14
Order By: Relevance
“…Pan et al (2007) reported that tissue total Se concentrations were similar in liver tissue of laying fowl when comparing sources but greater in the muscle tissue of SY-supplemented birds when compared with SS. Similar effects of Se source have been reported within the cardiac and skeletal muscles of cattle, sheep (Juniper et al, 2008a and and loin tissue of pigs (Mahan et al, 1999;Mateo et al, 2007), whereby tissue total Se concentrations have been greater in SY-supplemented animals when compared with those receiving a comparable dose of SS.…”
Section: Selenium Content In Tissuessupporting
confidence: 68%
See 1 more Smart Citation
“…Pan et al (2007) reported that tissue total Se concentrations were similar in liver tissue of laying fowl when comparing sources but greater in the muscle tissue of SY-supplemented birds when compared with SS. Similar effects of Se source have been reported within the cardiac and skeletal muscles of cattle, sheep (Juniper et al, 2008a and and loin tissue of pigs (Mahan et al, 1999;Mateo et al, 2007), whereby tissue total Se concentrations have been greater in SY-supplemented animals when compared with those receiving a comparable dose of SS.…”
Section: Selenium Content In Tissuessupporting
confidence: 68%
“…Radmilla et al (2008) and Sevcikova et al (2006) have both reported a lack of effect of Se supplementation on the meat quality attributes of broilers. Mahan et al (1999) showed little effect of Se source or dose on the drip loss of pig loin tissue and Skřivanová et al (2007) reported a lack of effect of SY supplementation on the oxidative stability of calf loin tissue. Taylor et al (2008) and Juniper et al (2008b) both reported that beef steaks from cattle supplemented with Se had similar shelf life attributes to those from unsupplemented animals, despite having higher Se contents.…”
Section: Meat Qualitymentioning
confidence: 97%
“…However, the Se values recorded in the T 0 group and Con birds were higher than those recorded in commercial lines of poultry in other studies that had received diets, which had not been augmented with supplementary Se (Petrovič et al, 2006;Yoon et al, 2007 andJuniper et al, 2011). The differences seen between comparable doses of SY and SS are indicative of improved uptake and incorporation of Se derived from SY and are consistent with the findings in sheep (Van Ryssen et al, 1989;Juniper et al, 2008a), cattle (Gunter et al, 2003;Phipps et al, 2008;Juniper et al, 2008b), pigs (Mahan and Parrett, 1996;Mahan et al, 1999;Kim and Mahan, 2001) and poultry (Petrovič et al, 2006;Juniper et al, 2011). However, the degree of response to supplementary Se is markedly lower than those recorded in other studies and most probably reflect the much higher blood and plasma Se levels seen at T 0 and in Con pheasants.…”
Section: Discussionsupporting
confidence: 85%
“…Radmilla et al (2008) and Sevcikova et al (2006) have both reported an absence of effect in broilers and a similar lack of response has also been reported in turkeys (Juniper et al, 2011). In addition, both pigs (Mahan et al, 1999) and cattle (Skřivanová et al, 2007;Taylor et al, 2008;Juniper et al, 2008b) have shown a lack of response in both tissue TBARS and GSH-Px activity in skeletal muscle to additional dietary Se. These results would suggest that higher tissue total Se contents tend not to reflect improvements in GSH-Px activity to the oxidative stability of skeletal tissue meat keeping quality.…”
Section: Discussionmentioning
confidence: 71%
“…Likewise, trace elements like selenium may affect oxidative stability, however, with inconsistent results concerning the nature of its impact: Skřivan et al (2012) found beneficial impact of inorganic and organic dietary Se sources on oxidative stability of meat. In contrast, organic Se was reported to yield better drip loss and meat lightness than inorganic Se (Mahan et al, 1999). Also manganese proved beneficial, when fed in high concentrations of mainly organic source (Apple et al, 2004 and.…”
Section: Introductionmentioning
confidence: 92%